A rare case of a novel coagulase negative Staphylococcus native valve endocarditis in a 28-year-old male. (2021) - Wutawunashe, Caleb V.; Ma, Rosaline; Chang, Gin Den William; Goyal, Rohan; Morrow, Zachary; Ilyas, Nazish
Abstract: Coagulase negative staphylococci (CoNS) are an emerging cause of native valve endocarditis in community and healthcare settings. We describe a case of a 28-year-old man with no significant risk factors who presented with Staphylococcus pettenkoferi native valve endocarditis. During our patient's initial hospitalization, he was treated for CoNS bacteraemia and subsequently discharged after a protracted hospital course with a transthoracic echocardiogram (TTE) showing no valvular vegetations. However, during the course of his second hospitalization, speciation identified S. pettenkoferi and transoesophageal echocardiogram (TEE) showed aortic valve perforations with new regurgitation raising concern for left sided endocarditis. We postulate that our patient may have been infected with the same CoNS species causing aortic valve endocarditis during his initial hospitalization. This case highlights the importance of recognizing CoNS as a possible causative bacterium in NVE, as well as the importance of obtaining a TEE when evaluating a patient for suspected endocarditis.